Participation in Pregnant Mother Class and Implementation of Exclusive Breastfeeding in Betungan Community Health Center, Bengkulu - Ismiati, Ismiati; Lubis, Yuliana; Susmini, Susmini (Journal of Maternal and Child Health, 2019)
Background: Exclusive breastfeeding can be seen from the role of the world in which in 2006, WHO (World Health Organization) issued a Child Growth Standard which is then applied throughout the world. The content is to emphasize the importance of breastfeeding only to infants from birth to 6 months of age. After that, the baby begins to be given complementary foods beside ASI. Data from the Health Profile of Bengkulu Province in 2014 showed that only 20.67% of infants aged 0-6 months get exclusive breastfeeding from the total number of infants aged 0-6 months ie 12.508 (Health Office, 2014). The purpose of this study is to obtain in-depth information about the implementation of prenatal class on exclusive breastfeeding at community health center.Subjects and Method: The qualitative research design used was Rapid Assessment Procedures, which is a qualitative approach or study. The population of mothers who have 0-6 months old baby sample was 16 people while the others were 4 heads of community health center, midwife, and cadre. Then the information received was processed and analyzed its theme (data reduction, data presentation, conclusion / verification) and then was tested for its validity with triangulation.Results: The lack of role of pregnant mother class in increasing exclusive breast feeding is caused by various factors. The practice of exclusive breastfeeding successfully performed by larger informants is due to the policies of maternity providers and post-maternal conditions for both mother and infant. For the maternal and child health program program, it is expected to be able to conduct periodic evaluation of the prenatal class.Keywords: exclusive breastfeeding, intention and classes of pregnant womenCorespondence:Ismiati. School of Health Polytechnics Bengkulu, North Sumatera, Jl. Indragiri No. 3 Padang Harapan Bengkulu. Email: ismiatidzaky@gmail.com. Mobile: 085290534545Journal of Maternal and Child Health (2019), 4(1): 36-39https://doi.org/10.26911/thejmch.2019.04.01.05